Escuela de padres como una transformación pedagógica para mejorar el acompañamiento a los estudiantes (2021)
The purpose of this research was to design a school of parents to strengthen the support of students in the learning process. It was carried out under a mixed, descriptive approach, based on observation. It uses the deductive hypothetical method, under the positivist or rationalist paradigm. A sample of 11 teachers from the primary basic level, 56 students from the second to fifth grade and 56 parents of IED families Luís Fernando González Botero from the municipality of La Apartada, department of Córdoba was selected. The sample was taken in a non-random and intentional manner. During the research, semi-structured interviews were conducted with eachers, a survey of parents and/or caregivers as well as students. The results indicate that the bonds of union between family and school should be strengthened and spaces created for reflection on aspects related to parental functions. For this reason, strategies are proposed such as the formation of the school of parents, the realization of periodic meetings with parents or caregivers, the creation of the institutional website and to resume home visits.